Atrial Tachycardias After Atrial Fibrillation Ablation: How to Manage? - Hung, Yuan (Arrhythm Electrophysiol Rev, 2020)
With catheter ablation becoming effective for non-pharmacological management of AF, many cases of atrial tachycardia (AT) after AF ablation have been reported in the past decade. These arrhythmias are often symptomatic and respond poorly to medical therapy. Post-AF-ablation ATs can be classified into the following three categories: focal, macroreentrant and microreentrant ATs. Mapping these ATs is challenging because of atrial remodelling and its complex mechanisms, such as double ATs and multiple-loop ATs. High-density mapping can achieve precise identification of the circuits and critical isthmuses of ATs and improve the efficacy of catheter ablation. The purpose of this article is to review the mechanisms, mapping and ablation strategy, and outcome of ATs after AF ablation.